OPTIMALISASI PERAN TENAGA KESEHATAN DALAM PENYALURAN BANTUAN DAN PELAYANAN MEDIS BAGI KORBAN BENCANA DI BATU BUSUK KOTA PADANG SUMATERA BARAT - Yusti Siana; Mhd Nurhuda; Dian Puspita (Nusantara Hasana Journal, 2026)
Flood disasters cause various health problems among affected communities, including an increased risk of infectious diseases and limited access to healthcare services. This community service activity aimed to improve the health status of flood victims through medical services, aid distribution, and health education in Batu Busuk, Padang City. The program was implemented by a medical team consisting of lecturers from the Faculty of Medicine, Baiturrahmah University, medical staff from Rahmi Hatta Clinic, and healthcare workers from Pauh Public Health Center using a community-based service approach. The methods included health examinations, medication distribution, health counseling, and referral services for specific cases. The results showed improved access to healthcare services and a reduction in post-disaster health complaints. This activity contributed to supporting community health recovery and enhancing disaster preparedness for future events.